Waking the sleeping dragon: gene expression profiling reveals adaptive strategies of the hibernating reptile Pogona vitticeps - Capraro, Alexander (BMC Genomics, 2019)
BACKGROUND: Hibernation is a physiological state exploited by many animals exposed to prolonged adverse environmental conditions associated with winter. Large changes in metabolism and cellular function occur, with many stress response pathways modulated to tolerate physiological challenges that might otherwise be lethal. Many studies have sought to elucidate the molecular mechanisms of mammalian hibernation, but detailed analyses are lacking in reptiles. Here we examine gene expression in the Australian central bearded dragon (Pogona vitticeps) using mRNA-seq and label-free quantitative mass spectrometry in matched brain, heart and skeletal muscle samples from animals at late hibernation, 2 days post-arousal and 2 months post-arousal. RESULTS: We identified differentially expressed genes in all tissues between hibernation and post-arousal time points; with 4264 differentially expressed genes in brain, 5340 differentially expressed genes in heart, and 5587 differentially expressed genes in skeletal muscle. Furthermore, we identified 2482 differentially expressed genes across all tissues. Proteomic analysis identified 743 proteins (58 differentially expressed) in brain, 535 (57 differentially expressed) in heart, and 337 (36 differentially expressed) in skeletal muscle. Tissue-specific analyses revealed enrichment of protective mechanisms in all tissues, including neuroprotective pathways in brain, cardiac hypertrophic processes in heart, and atrophy protective pathways in skeletal muscle. In all tissues stress response pathways were induced during hibernation, as well as evidence for gene expression regulation at transcription, translation and post-translation. CONCLUSIONS: These results reveal critical stress response pathways and protective mechanisms that allow for maintenance of both tissue-specific function, and survival during hibernation in the central bearded dragon. Furthermore, we provide evidence for multiple levels of gene expression regulation during hibernation, particularly enrichment of miRNA-mediated translational repression machinery; a process that would allow for rapid and energy efficient reactivation of translation from mature mRNA molecules at arousal. This study is the first molecular investigation of its kind in a hibernating reptile, and identifies strategies not yet observed in other hibernators to cope stress associated with this remarkable state of metabolic depression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5750-x) contains supplementary material, which is available to authorized users.